PARANEOPLASTIC ANTI-GQ1B SYNDROME ASSOCIATED WITH DIFFUSE LARGE B-CELL LYMPHOMA. Issue 12 (15th November 2016) - Robinson, Ruth; Coebergh, Jan; Abdel-Aziz, Khaled
Abstract : Case: A 79 year old man with a background of hypertension presented with subacute onset of ataxia, oscillopsia as result of downbeat nystagmus and dysarthria. On examination he was areflexic. MRI brain showed chronic small vessel ischaemia. CSF analysis revealed elevated CSF protein (0.66 g/L), with unmatched oligoclonal bands. CSF glucose and cell counts were normal. CT chest, abdomen and pelvis was unremarkable. Serum was negative for ANA, ANCA, onconeuronal antibodies but positive for Anti-GQ1b IgG antibody; a diagnosis of atypical Miller-Fisher syndrome was initially made. We treated our patient with intravenous immunoglobulins but improvement over 8 weeks was modest. His Anti-GQ1b antibody titre rose [400 (normal: <200)] and there was no further improvement following a second course of immunoglobulins. Five months after the initial presentation, a biopsy of a newly enlarging cervical lymph node confirmed the diagnosis of large B-cell lymphoma. After 15 cycles of targeted radiotherapy, anti-GQ1b antibodies were no longer detectable in the patient's sera and the clinical signs present on initial presentation had resolved. Discussion: Our case highlights that anti-GQ1b antibodies can be associated with a treatment-resistant, paraneoplastic neurological syndrome mimicking Miller-Fisher Syndrome, which may present several months prior to the identification of a malignancy.